Bridging the language gap for simulation resources. (22nd March 2021) - Reeves, Andrew; Auerbach, Marc; Kou, Maybelle; Sanseau, Elizabeth; Hamann, Magnus; Roland, Damian
Abstract : With increasing use of open access platforms, simulation-based resources are being shared across geographical borders. There are benefits to designing resources with language and content which is understandable and applicable to learners in different countries. This report aims to assess the differences between scenarios from different groups and explore whether common terms can be used to make internationally relevant simulation resources in future. In collaboration between two groups producing Free Open Access Medical Education simulation resources in the UK and USA, we present observations of terms used in our simulation resources. The content within a series of simulation scenarios from both groups was reviewed, with notable differences in language collected. There are areas of overlap between the terms used in the UK and USA. Semantic, cultural and system differences were found which could prevent scenarios from being transferred between countries. The differences we describe highlight that language choice is important if simulation producers are intent on developing scenarios with international impact. There is work to be done to ensure that resources can be used internationally—embracing linguistics has the potential to aid this process, with the use of simplified language and feedback from local communities being key steps.